Electro-deoxidation Process for Producing FeTi from Low-Grade Ilmenite: Tailoring Precursor Composition for Hydrogen Storage - Padhee S.P.; Chanda U.K.; Singh R.; Roy A.; Mishra B.; Pati S. (My University, 2025)
Abstract: Electro-deoxidation of ilmenite (FeTiO3) is an economical production method of FeTi, particularly, if the end use is hydrogen storage. In this study, we show that electro-deoxidation of impure FeTiO3 with Ti content lower than Fe, as in the case of low-grade FeTiO3 ore, results in the formation of a two-phase material consisting of FeTi and Fe2Ti. The presence of Fe2Ti is detrimental to the hydrogen storage efficacy. We show for the first time that it is possible to avoid the formation of Fe2Ti or β-Ti as a second phase under similar operating conditions only by tailoring the composition of the cathode precursor, i.e., the addition of TiO2 to low-grade FeTiO3 so that the atomic ratio of Fe:Ti in the precursor is ~ 1:1. Low-grade FeTiO3 with 10 wt% TiO2 resulted in single-phase FeTi with the atomic ratio of Fe:Ti ~ 1:1 in the precursor and in the final reduced alloy. The hydrogen storage capacity of the single-phase FeTi is nearly 36% higher as compared to the two-phase alloy consisting of FeTi–Fe2Ti. Graphical Abstract: [Figure not available: see fulltext.]. © 2021, The Minerals, Metals & Materials Society.